Analisis Manajemen Termal LiFePO4 (Lithium Iron Phosphate) dengan Pendinginan Bubble Generator dan Tanpa Bubble Generator - Ilmi Maulana, Muhammad; Catrawedarma, IGNB.; Novita Sari, Eli; Satria Prasetya DY, IGNA; Ridlo Pamuji, Dian (Universitas Sriwijaya, 2024)
Lithium Iron Phosphate (LiFePO4) batteries are known for their long life, low self-discharge rate, and stable performance. However, LiFePO4 batteries are prone to thermal problems when operating outside the optimal temperature range of 25-40°C [12], which can threaten the performance, safety, and lifetime of the battery. Previous research has shown cooling systems to be a solution to these thermal issues. However, the use of an internal cooling system risks changing the voltage and causing the battery to overheat. Therefore, an approach using an external cooling system is recommended to maintain the performance of Li-ion batteries without changing their internal components. In an effort to improve the thermal management of LiFePO4 batteries, this study proposes to analyze the use of cooling with bubble generator and without bubble generator. The bubble generator here is intended to increase the random movement of water in the cooling system so that heat absorption becomes more optimal. This study uses a circulating cooling system with water pump media, airator, bubble generator and cooling using water, for the flow container that circulates in the battery cells we use acrilyc mica. The results of the influence of variations in bubble generator testing average temperature values on LiFePO4 batteries of 16.26ºC to 23.94ºC. and the influence of variations in testing without bubble generators average temperature values on LiFePO4 batteries of 17.62ºC to 25.57ºC, From this study it can be concluded that the bubble generator is able to cool 90% of the operational temperature 25-40 °C.